Generation of a Peptide Vaccine Candidate against Falciparum Placental Malaria Based on a Discontinuous Epitope - Catherine J. Mitran; Lauren M. Higa; Michael F. Good; Stephanie K. Yanow (Vaccines, 2020)
In pregnant women, Plasmodium falciparum-infected red blood cells adhere to the placenta via the parasite protein VAR2CSA. Two vaccine candidates based on VAR2CSA are currently in clinical trials; however, these candidates failed to elicit strain-transcending antibody responses. We previously showed that a cross-reactive monoclonal antibody (3D10) raised against the P. vivax antigen PvDBP targets epitopes in VAR2CSA. We now aim to design a peptide vaccine against VAR2CSA based on the epitope that generated 3D10. We mapped the epitope to subdomain 1 (SD1) of PvDBP and identified a peptide that contained the minimal sequence. However, this peptide did not elicit cross-reactive VAR2CSA antibodies in mice. When tested against a broader, overlapping peptide array spanning SD1, 3D10 in fact recognized a discontinuous epitope consisting of three segments of SD1. These findings presented the challenge to generate this larger structural epitope as a synthetic peptide since it is stabilized by two pairs of disulfide bonds. We overcame this using a synthetic scaffold to conformationally constrain the SD1 peptide and coupled it to keyhole limpet hemocyanin (KLH). The SD1-KLH conjugate elicited antibodies in mice that cross-reacted with VAR2CSA. This strategy successfully recapitulated a discontinuous epitope with a synthetic peptide and represents the first heterologous vaccine candidate against VAR2CSA.